Macrophage IKKα Deficiency Suppresses Akt Phosphorylation, Reduces Cell Survival, and Decreases Early Atherosclerosis. Issue 4 (April 2016) - Babaev, Vladimir R.; Ding, Lei; Zhang, Youmin; May, James M.; Lin, P. Charles; Fazio, Sergio; Linton, MacRae F.
Abstract : Objective—: The IκB kinase (IKK) is an enzyme complex that initiates the nuclear factor κB transcription factor cascade, which is important in regulating multiple cellular responses. IKKα is directly associated with 2 major prosurvival pathways, PI3K/Akt and nuclear factor κB, but its role in cell survival is not clear. Macrophages play critical roles in the pathogenesis of atherosclerosis, yet the impact of IKKα signaling on macrophage survival and atherogenesis remains unclear. Approach and Results—: Here, we demonstrate that genetic IKKα deficiency, as well as pharmacological inhibition of IKK, in mouse macrophages significantly reduces Akt S 473 phosphorylation, which is accompanied by suppression of mTOR complex 2 signaling. Moreover, IKKα null macrophages treated with lipotoxic palmitic acid exhibited early exhaustion of Akt signaling compared with wild-type cells. This was accompanied by a dramatic decrease in the resistance of IKKα −/− monocytes and macrophages to different proapoptotic stimuli compared with wild-type cells. In vivo, IKKα deficiency increased macrophage apoptosis in atherosclerotic lesions and decreased early atherosclerosis in both female and male low-density lipoprotein receptor (LDLR) −/− mice reconstituted with IKKα −/− hematopoietic cells and fed with the Western diet for 8 weeks compared with control LDLR −/− mice transplanted with wild-type cells. Conclusions—: Hematopoietic IKKα deficiency in mouse suppresses Akt signaling, compromising monocyte/macrophage survival and this decreases early atherosclerosis. Abstract : Supplemental Digital Content is available in the text.